Investment Guarantees in Unit-Linked Life Insurance from the Customer Perspective - Gatzert, Nadine; Huber, Carin; Schmeiser, Hato (Zeitschrift für die gesamte Versicherungswissenschaft, 2010)
Interest rate guarantees are a typical contract feature in unit-linked-life insurance products. As the financial crisis of 2007/2008 has shown, these guarantees can be of substantial value for policyholders since they ensure that at least a minimum amount will be paid back even if the mutual fund value falls below a specific guaranteed level. However, from the insurance company's view, these guarantees can be costly - especially in highly volatile markets - due to the required risk management measures which must be undertaken to secure the guarantees promised to the customers. Thus, the aim of this paper is to investigate whether customers really value these guarantees and if their willingness to pay (WTP) is sufficient to cover the guarantee costs. To elicit customer WTP, we use an online questionnaire and compare these results to the actual guarantee costs calculated with the Black and Scholes option pricing formula. One main finding is that even though most of the participants in the online questionnaire work in the financial industry, subjective prices are difficult to derive and are lower, on average, than the prices obtained using a financial pricing model. However, many participants are still willing to pay a substantially higher price.
WiSo-Import:2015-03-26:952
Keywords: Forschungsbericht 2010; Kohäsion